Juridical Review of the Role of Medan City Bawaslu in Preventing and Monitoring Political Money Practices in the 2024 Election in Medan City - Hisar Siregar; Nalom Siagian; Herlina Manullang; Misefa Harefa (Journal of Law, Politic and Humanities, 2025)
Indonesia is a country that adheres to a democratic system, which means that the supreme power is in the hands of the people and the people have the right to determine who becomes their leader or representative, through an election, hereinafter referred to as (Election). As stated in Article 1 paragraph (2) of the Constitution of the Republic of Indonesia that "Sovereignty is in the hands of the People and is exercised according to the Constitution". Thus elections are an important instrument in a democracy that adheres to a representative system. In this research the author uses a type of normative juridical research that is qualitative in nature, namely research that aims to examine legal principles, legal systematics, and legal synchronization. In this study the authors focus on discussing the juridical review of the role of Bawaslu Medan city in preventing and supervising the practice of money politics in the 2024 elections in Medan City. To examine this research, the authors make a formulation of the problem, namely, how is the regulation of Bawaslu's role in preventing and supervising the practice of political money in the 2024 elections in Medan city, how is the role of Bawaslu in preventing and supervising the practice of political money in the 2024 elections in Medan city, and what are the obstacles Bawaslu in preventing and supervising the practice of political money in the 2024 elections in Medan city. In organizing elections, it is carried out by the Election Organizing Commission (KPU), and supervised by the Election Supervisory Body (Bawaslu) which is adhoc. The institution carries out its duties, powers and obligations according to Law No. 7 of 2017 concerning General Elections and based on the 1945 Constitution of the Republic of Indonesia. Every election implementation often occurs various violations, criminal acts, and also election disputes, one of which is money politics. Money politics or known as money politics is an election crime regulated in article 280 paragraph (1) of Law No. 7 of 2017 concerning elections. The efforts of Bawaslu Medan City in preventing and supervising the practice of money politics in the 2024 elections in Medan city, conducting socialization to the community, students, and also election participants, and supervising reports of alleged money politics that occurred in the Medan city area. However, Bawaslu Medan City also experienced several obstacles in carrying out its role caused by economic factors, factors of habit, tradition, and opportunity, as well as factors of lack of public understanding of politics.